IMF Research Bulletin, September 2011. (IMF Research Bulletin; IMF Research Bulletin ;, 2001)
The September 2011 issue of the IMF's quarterly "Research Bulletin" features a Q and A discussion about economic recovery in countries emerging after war or other open. The research summaries in this issue include: "Revisiting Capital Controls"; and "Capital Flows and Financial Stability: Monetary Policy and Macroprudential Responses." The September issue also provides details on IMF visiting scholars (mainly during the September - December 2011 period), as well as recent Working Papers and Staff Discussion Notes published by the IMF.